Surimi and surimi seafood - Park, Jae Won, 1953- (Boca Raton : CRC Press, 2014)
'Surimi and surimi seafood products were originated in Japan several hundred years ago, and their modern production technology has been professionally documented since the 1950s. The book covers the basic science of surimi (fish proteins) and contains updates on fisheries and the market. It reviews a wide range of surimi seafood manufacturing technologies. It discusses quality assessment/quality control, development, and nutrition technology'--
'It was not like 2000 and 2005, when the first and second editions were prepared and published. Even though my project for the third edition was planned in advance and execution commenced perhaps in 2011, the project has moved at an extremely slow pace. I took my sabbatical leave at Korea University in 2011-2012 with my primary goal'to complete all of the manuscripts for the third edition.' But it did not work out as nicely as I had planned and my projected'third edition' was delayed day after day. It was not like 2000 and 2005 perhaps because I have slowed with age and perhaps because I have tried to include too many things in this third edition. I feel I have made an extraordinary effort for this book as I attempted to add the most up-to-date information in the science of surimi and surimi seafood. This book, consisting of 23 total chapters, is significantly expanded from the 17 chapters in the second edition. The highlight is that this revised/extended book is coauthored by 63 combined scientists/industry leaders. I tried to make this textbook serve like an encyclopedia for surimi and surimi seafood. Therefore, this book has broadened its contents and depth. Highlights include historical reviews in surimi technology and industry, comminution technology and application, coproduct utilization, research and development, and nutrition and health benefits. For the production of surimi seafood products, this edition covers crabsticks, kamaboko/chikuwa/tempura, fish balls, and fish sausage in different chapters. I am very proud of my former students and visiting scientists who worked with me and put up with my never-ending demand while they were at my laboratory. Three visiting professors and 13 former students have participated in the book as coauthors of various'--
Includes bibliographical references and index.
Keywords: Surimi; Fishery processing